Application Route and Dose of Silicon in the Production of Cucumber Grown in Tezontle - Nuñez-Ambriz, Rogelio; Apaéz-Barrios, Patricio (REVISTA TERRA LATINOAMERICANA, 2025)
The accelerated growth of the population increases the demand for vegetables such as cucumber (Cucumis sativus L.). In addition, challenges such as limited arable land and water availability, as well as the negative impacts of climate change, create the need to use substrates as cultivation media and to implement sustainable alternatives to increase yields, such as the use of beneficial elements. The objective of this study was to evaluate two silicon application routes, root and foliar, and three doses (0, 500, 1000, and 1500 mg L-¹) on production, fruit quality, and foliar nutrient content of cucumber grown in tezontle under protected conditions. Treatments were arranged in the field using a randomized complete block design with five replications. Yield increased by 36 and 43.9% with the application of 1500 mg supplied directly to the root and via foliar application, respectively, and by 33% with 1000 mg via foliar application. Fruit firmness increased by 19 and 20% with the application of 1500 mg to the foliage and the root, respectively; whereas this same dose, when applied to the root, increased fruit pH by 4.9%. When 1500 mg was applied to the root, leaf macronutrient content increased by 4.8% for S and 32.9% for N. In contrast, foliar application of 500 mg of silicon increased heavy metal content by 14% for Zn and 61% for Fe; however, these contents decreased with doses of 1000 and 1500 mg, regardless of the application method. Therefore, silicon application increased cucumber yield and fruit quality, modified foliar nutrient content, and the most appropriate dose was 1500 mg supplied either to the root or foliarly.